Metody wykorzystywane przez polskich kryminalistyków i archeologów przy eksploracji mogił – różnice i zbieżności - Górecki, Adam (Acta Universitatis Lodziensis. Folia Archaeologica, 2018)
There seem to be a lot of differences between archaeology and forensic science but, when we take a closer look, we may find out that some methods and goals may be similar, especially on the ground of exhumation of graves. Since the early 90s, in Poland, archaeologists more often started to take part in investigations covering mass murders and crimes against humanity committed during the Second World War. It occurred that their methodology is providing best results in this kind of work. At first, archeologists started only as consultants but then they were given a possibility to lead their own field of excavations in that area of interest. Moreover, it led to creating a new subdiscipline called forensic archaeology. It is hard to tell the difference between archaeological and forensical field methods of exhuming graves. Archaeological literature is way more precise in describing that topic, whereas police experts are thought to provide general procedures of securing a crime scene. The most obvious differences between the two fields in question are visible in the methods of documentation. However, there is no doubt that the specialists in each of the disciplines have learned a lot from each other since they decided to cooperate in some specific cases.